Nazwiska patronimiczne szlachty na -owicz, -ewicz w starostwie grabowieckim od XVI do XVIII wieku - Olejnik, Marek (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The surnames of nobility with the suffixes -owicz//-ewicz in starosty district of Grabowiec have been analyzed in the article. The source database used in the article contains the municipal books of Grabowiec from 16th to the 18th centuries. On the base of analyzed material it can be concluded that gentry anthroponyms with suffixes -owicz//-ewicz have two-piece form (name and surname). The basis for the surnames are first and foremost names, often church names, and nicknames